PERLINDUNGAN HUKUM TERHADAP KREDITOR DAN UPAYA NOTARIS MEMBUAT PERJANJIAN PERKAWINAN SETELAH PERKAWINAN - Nadia Putri, Respati; Dewi Judiasih, Sonny; Anisa Lubis, Nanda (Veritas et Justitia, 2019)
One of the legal consequence of a marriage is a consolidation of husband and wife assets with the understanding that both parties before signing the marriage contract can decide otherwise, through the pre-nuptial contract. The Constitutional Court Decision No. 69/PUU-XII/2015, made possible the making of a similar arrangement after the marriage contract has been signed.  The focus of this article is to explore, using a juridical normative approach, what legal protection exist for third parties.  The main finding is that legal protection is provided by requiring the contract be made by and before a notary public, registered at the Civil Registrar Office and all that is performed only after the Notary Public made an inventory of both spouse’s assets.